Intersections in simulation and gaming : 21st Annual Simulation Technology and Training Conference, SimTecT 2016, and 47th International Simulation and Gaming Association Conference, ISAGA 2016, held as part of the first Australasian Simulation Congress, ASC 2016, Melbourne, VIC, Australia, September 26-29, 2016, Revised selected papers /: 21st Annual Simulation Technology and Training Conference, SimTecT 2016, and 47th International Simulation and Gaming Association Conference, ISAGA 2016, held as part of the first Australasian Simulation Congress, ASC 2016, Melbourne, VIC, Australia, September 26-29, 2016, Revised selected papers. (2018) - Unknown
No abstract available